ANALYSIS OF CHARACTER EDUCATION APPLICATION IN THE LEARNING PROCESS - Patimbangi, Andi; Darwis, Rahma Hidayati (International Journal of Psychosocial Rehabilitation, 2020)
Education has a very important role in building academic character and dignity. For this reason, the integration of character education into the learning process is one of the efforts to realize that goal. In this study illustrated how the application of character education in the learning process and the obstacles encountered in implementing it. This research is a descriptive study with a qualitative approach that aims to find and describe information thoroughly and intact about the application of character education in the learning process. Based on the results of the field study, it was found that the application of character education had been carried out through three stages, namely planning, implementation and assessment. Nevertheless, in its application, it is still often found obstacles so that the implementation of character education has not been able to run optimally. These constraints include: 1) the lecturer's understanding of the concept of character education is inadequate, 2) the difficulty of the lecturer identifying the character values in the courses taught; 3) lack of knowledge about variations in the learning model that can be used to grow characters; 4) facilities and infrastructure that have not been adequately supported. With these constraints, several policies are needed, including policies on improving the competence and professionalism of lecturers, policies regarding character development programs both formal and informal, and policies regarding enforcement of integrity.